TINDAK TUTUR EKSPRESIF DALAM FILM GARA GARA WARISAN SERTA RELEVANSINYA PADA MATERI DRAMA DI SMA - Galuh Kusumawati Sukarjo; Kundharu Saddhono; Nugraheni Eko Wardani (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2024)
This study aims to: (1) analyze and describe the forms of expressive speech acts found in the film Gara Gara Warisan by Muhadkly Acho, and (2) describe the relevance of the film Gara Gara Warisan in Learning Drama Material for Grade XI in High School. This research is a qualitative research. The data sources of this research include documents in the form of the Gara Gara Warisan film and its informants, namely the Indonesian language teacher of class XI. Data collection techniques are carried out by document analysis and interviews. Meanwhile, the data validity test technique is the triangulation of theory and data sources. This study uses a data analysis technique, namely document analysis. The results of this study are as follows. The film Gara Gara Pahlawan contains expressive speech acts which consist of 5 expressive speech acts of apologizing, apologizing, giving praise, saying thank you, and saying congratulations. Overall there were 13 data found. The most data is in the expressive speech act of apologizing with 5 data, while the data with the lowest amount is the expressive speech act of apologizing with 1 data.